PARADIGMA BARU PEMBEJARAN DALAM PENDIDKAN ISLAM BERWAWASAN MULTIKULTURAL - Kahar, Kahar (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2015)
This paper focuses on the education of paradigm new multicultural vision of Islam that has a significant role in the current state today. Multicultural education requires rationality , ethical , intellectual , social pragmatic inter - relative , ie, teaching the ideals of inclusiveness , pluralism and mutual respect for all people and cultures is a humanistic imperative that a prerequisite for ethical living and full participation in civic and democratic multicultural world diverse . Already the laws that man was created in diversity , difference and equality . Seeing the reality of human life are not aware of the essence itself . We see the development of all future time of the old order , the new order samapai order Reforms Democracy has brought winds revive the educational discourse of multiculturalism as a strength of the Indonesian nation